2020
DOI: 10.1155/2020/9463548
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Secretome Enhancement by Nicotinamide and Vasoactive Intestinal Peptide: A New Therapeutic Approach for Retinal Degenerative Diseases

Abstract: Mesenchymal stem cells (MSC) secrete neuroprotective molecules that may be useful as an alternative to cell transplantation itself. Our purpose was to develop different pharmaceutical compositions based on conditioned medium (CM) of adipose MSC (aMSC) stimulated by and/or combined with nicotinamide (NIC), vasoactive intestinal peptide (VIP), or both factors; and to evaluate in vitro their proliferative and neuroprotective potential. Nine pharmaceutical compositions were developed from 3 experimental approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Especially in recent years, under the influence of factors such as population aging, dietary structure, and pollution, the incidence rate has increased. CVD has great harm to human health, and unhealthy behaviors can easily lead to the occurrence of cardiovascular diseases, as shown in Figure 3 [13,14]. According to the "2014 China Cardiovascular Disease Report," CVD has become the leading cause of disease-related death among urban and rural residents in China, with 44.8% in rural areas and 41.9% in urban areas.…”
Section: Current Status Of Patients With Cardiovascular Disease (Cvd)mentioning
confidence: 99%
“…Especially in recent years, under the influence of factors such as population aging, dietary structure, and pollution, the incidence rate has increased. CVD has great harm to human health, and unhealthy behaviors can easily lead to the occurrence of cardiovascular diseases, as shown in Figure 3 [13,14]. According to the "2014 China Cardiovascular Disease Report," CVD has become the leading cause of disease-related death among urban and rural residents in China, with 44.8% in rural areas and 41.9% in urban areas.…”
Section: Current Status Of Patients With Cardiovascular Disease (Cvd)mentioning
confidence: 99%
“…Their therapeutic potential is being tested for the treatment of diverse diseases in musculoskeletal [12,52,57,[65][66][67][75][76][77][78] and cardiovascular systems [60,72,[79][80][81], nephrology [82,83], skin [62,68,[84][85][86] and immunology [71,87], among others. Surprisingly, we could only find one published study about the potential of human AT-MSC-EVs for the treatment of eye diseases [88], despite the fact that human AT-MSC and their conditioned media are being used in ophthalmology [89][90][91][92][93][94][95][96][97][98][99]. For instance, they are being used in 6 out of 403 registered clinical trials with these cells (ClinicalTrials.gov, N C T 0 4 4 8 4 4 0 2 N C T 0 3 8 7 8 6 2 8 , N C T 0 2 9 3 2 8 5 2 , NCT01808378, NCT02144103 and NCT02024269).…”
Section: Cargo Of At-msc-evsmentioning
confidence: 99%
“…Surprisingly, we could only find one published study about the potential of human AT-MSC-EVs for the treatment of eye diseases [ 88 ], despite the fact that human AT-MSC and their conditioned media are being used in ophthalmology [ 89 99 ]. For instance, they are being used in 6 out of 403 registered clinical trials with these cells ( ClinicalTrials.gov , NCT04484402 NCT03878628, NCT02932852, NCT01808378, NCT02144103 and NCT02024269).…”
Section: Cargo Of At-msc-evsmentioning
confidence: 99%
“…These findings support the hypothesis that developing a cell-free therapeutic strategy based on the production of MSC secretome cocktails with neuroprotective characteristics may be an approach to treat RND. 11 – 14 The results reported here and in our previous studies 11 , 12 , 60 showed that the neuroprotective capacity of bmMSC secretome is higher than that of the secretome from adipose MSCs. In addition, an environment of retinal neurodegeneration, as shown in NR organ cultures, seems crucial for obtaining human bmMSC secretome with neuroprotective properties.…”
Section: Discussionmentioning
confidence: 55%